Perbandingan produktifitas ulat Sutra dari dua tempat pembibitan yang berbeda pada kondisi lingkungan pemeliharaan panas - Ita Wahju Nursita (Faculty of Animal Science, Universitas Brawijaya, 2011)
Abstract: The objective of the study was to know the comparison of cocoon production, normal cocoon, and the length of cocoon’s fiber of silkworm (Bombyx mori) between PSA Soppeng and PSA Temanggung in hot natural environment. About 300 silkworm of silkworm was applied for 2 treatments (P1= silkworm from PSA Soppeng) and (P2= silkworm from PSA Temanggung), and 6 replications. The place of the experiment was in Ceweng village, Diwek , Jombang. The method of the research was experiment, to compare the data result used the t-test. The statistical analysis result of the data showed that silkworm from two different breeding places didn’t have any significant different (P>0,05) to the percentage of total cocoon production and of normal cocoon production, but it was true for the length of cocoon’s filament of silkworm (p<0,01). The mean for the percentage of total cocoon production was between 87,3 % and 89,7 % , and of normal cocoon production was between 95,2 % and 96,4 % , and mean for the length of cocoon’s filament of silkworm on each treatment P1 and P2 in a series were (910.9±10.1m), (824.9±21.5m).From the research result it could be concluded that silkworm from PSA Soppeng had better adaptability to hot environment and low humidity than of PSA Temanggung based on filament production. It was suggested to continue the research with the one related to moleculer genetic such the pattern of the DNA band to know if there is existed a genetic difference, or about the anatomy/physiology differences of silkworm gland of silkworm from two different breeding sites. Key words: silkworm, hot environment, productivity